Polypharmacy and Polytherapy: Current Perspectives on Risk–Benefit Balance and Strategies for Optimization of Multidrug Treatment in Patients - Agata Sozańska; Julia Nogły; Julia Mierzwińska-Mucha; Bartosz Roś; Katarzyna Siekaniec (Journal of Education, Health and Sport)
Introduction